Slot antenna array synthesis using the infinitesimal dipole model technique: Theory and experiment. Issue 11 (18th August 2020) - Mikki, Said; Clauzier, Sebastien; Karimi, Muhammad A.; Shamim, Atif; Antar, Yahia M. M.
Abstract: The present article proposes and validates a new general design methodology that can be used to automatically find proper positions and orientations of waveguide‐based radiating slots capable of realizing any given radiation beam profile. The new technique combines basic radiation theory and waveguide propagation theory in an analytical model that permits the prediction of the radiation characteristics of generic slots without the need to perform full‐wave numerical solution while completely avoiding using transmission‐line models or the slot impedance method. The analytical model is then used to implement a low‐cost objective function within a global optimization scheme and subsequently deployed to find optimum positions and orientations of clusters of radiating slots cut into the waveguide surface such that any desired beam pattern can be obtained, leading to very efficient and robust beamforming capability that can be applied to dynamic beamforming in real‐time scenarios like MIMO systems. The proposed design method is verified using both full‐wave numerical solution and experiment.